Faustoviruses: Comparative Genomics of New Megavirales Family Members - Benamar, Samia; Reteno, Dorine G. I.; Bandaly, Victor; Labas, Noémie; Raoult, Didier; La Scola, Bernard (Frontiers in Microbiology, 2016)
An emerging interest for the giant virus discovery process, genome sequencing and analysis has allowed an expansion of the number of known Megavirales members. Using the protist Vermamoeba sp. as cell support, a new giant virus named Faustovirus has been isolated. In this study, we describe the genome sequences of nine Faustoviruses and build a genomic comparison in order to have a comprehensive overview of genomic composition and diversity among this new virus family. The average sequence length of these viruses is 467,592.44 bp (ranging from 455,803 bp to 491,024 bp), making them the fourth largest Megavirales genome after Mimiviruses, Pandoraviruses and Pithovirus sibericum. Faustovirus genomes displayed an average G+C content of 37.14 % (ranging from 36.22% to 39.59%) which is close to the G+C content range of the Asfarviridae genomes (38%). The proportion of best matches and the phylogenetic analysis suggest a shared origin with Asfarviridae without belonging to the same family. The core-gene-based phylogeny of Faustoviruses study has identified four lineages. These results were confirmed by the analysis of amino acids and COGs category distribution. The diversity of the gene composition of these lineages is mainly explained by gene deletion or acquisition and some exceptions for gene duplications. The high proportion of best matches from Bacteria and Phycodnaviridae on the pan-genome and unique genes may be explained by an interaction occurring after the separation of the lineages. The Faustovirus core-genome appears to consolidate the surrounding of 207 genes whereas the pan-genome is described as an open pan-genome, its enrichment via the discovery of new Faustoviruses is required to better seize all the genomic diversity of this family.